Assessment of the effect of oral corticosteroids on bone mineral density in systemic lupus erythematosus: a preliminary study with dual energy x ray absorptiometry. Issue 8 (August 1990) - Dhillon, V B; Davies, M C; Hall, M L; Round, J M; Ell, P J; Jacobs, H S; Snaith, M L; Isenberg, D A
Abstract : Dual energy x ray absorptiometry and a wide range of blood and urine tests were used to assess the propensity of patients with systemic lupus erythematosus to develop an impairment of bone mineral density. Surprisingly, in this preliminary study no significant differences in bone mineral density were found when patients taking 10 mg or more of prednisolone for six months or longer were compared with those who had never taken prednisolone.